PENGARUH PENDAPATAN TERHADAP MINAT MENABUNG MASYARAKAT DESA HILIOTALUA PADA CU. KASIH SETIA PULAU TELLO KECAMATAN PULAU-PULAU BATU - Kurnia Wati Wau (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
The purpose of this study was to determine the effect of income on the interest in saving in Hiliotalua Village Community at CU. Love Loyalty Tello Island Island District – Batu Island. This type of research is causal quantitative. The data Source was obtained from the Hiliotalua Village Community at CU. Love Loyalty Tello Island Island District – Batu Island, which has savings of 35 people. The data collection techniques in this study was by distributing questionnaires as a research instrument to all respondents, namely the Hiliotalua Village Community. Methods of data analysis in this study using simple regression analysis. The results of this study indicate that there is an influence of income on the intention to save in Hiliotalua Village Community at CU. Love Loyalty Tello Island Island District – Batu Island, is proven by a T count value of 6,527 > T table of 1,692 and a significant level of 0.000< 0,05. Thus, it is shown that income has an effect on the interest in saving the people of Hiliotalua Village at CU. Love Loyalty Tello Island Island District – Batu Island. In this study, a simple linear regression equation was obtained, namely: Y = 16,202+0,639X. Then the square value of income can explain the interest in saving variable.